Survival time of Leptospira kirschneri serovar Grippotyphosa under different environmental conditions - Nau, L. H. (PLoS One, 2020)
Leptospirosis is a re-emerging zoonotic disease of high medical importance that affects humans worldwide. Humans or animals acquire an infection with pathogenic leptospires either by direct contact with infected animals or by indirect contact to contaminated environment. Survival of Leptospira spp. in the environment after having been shed via animal urine is thus a key factor to estimate the risk of infection, but not much is known about the tenacity of pathogenic leptospires. Here, the survival time of both a laboratory strain and a field strain of L. kirschneri serovar Grippotyphosa in animal urine and their tenacity while drying was investigated and compared at different temperatures (15°C-37°C). Leptospira spp. are also often found in rivers and ponds. As the infection risk for humans and animals also depends on the spreading and survival of Leptospira spp. in these environments, the survival of L. kirschneri serovar Grippotyphosa was investigated using a 50-meter-long hose system simulating a water stream. Both strains did not survive in undiluted cattle or dog urine. Comparing different temperatures and dilution media, the laboratory strain survived the longest in diluted cattle urine with a slightly alkaline pH value (3 days), whilst the field strain survived in diluted dog urine with a slightly acid pH value up to a maximum of 24 h. Both strains did not survive drying on a solid surface. In a water stream, leptospires were able to move faster or slower than the average velocity of the water due to their intrinsic mobility but were not able to survive the mechanical damage caused by running water in the hose system. From our results we conclude, that once excreted via animal urine, the leptospires immediately need moisture or a water body to survive and stay infectious.